2010
DOI: 10.1038/modpathol.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

Vascular invasion is an early event in pathogenesis of Merkel cell carcinoma

Abstract: This study investigated vascular and especially lymphovascular invasion in primary Merkel cell carcinoma and its value as a prognostic factor. Paraffin-embedded blocks prepared from tumor samples obtained from126 patients diagnosed with Merkel cell carcinoma in 1979-2004 were immunohistochemically stained using antibodies CD31 and D2-40 to detect intravascular tumor emboli. This finding was compared with the clinical data and the disease outcome. Intravascular tumor cells were observed in 117 (93%) of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…20 We subsequently detected LVI in 90% of the tumours, which supports data of other authors employing similar techniques. 42,49 Although analysing correlations between clinical outcomes did not reach statistical significance, there was a trend towards development of regional LNM in patients with higher LVI (P = 0.072). Moreover, one should take into consideration that all three patients without LVI remained free of disease during the follow-up period.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…20 We subsequently detected LVI in 90% of the tumours, which supports data of other authors employing similar techniques. 42,49 Although analysing correlations between clinical outcomes did not reach statistical significance, there was a trend towards development of regional LNM in patients with higher LVI (P = 0.072). Moreover, one should take into consideration that all three patients without LVI remained free of disease during the follow-up period.…”
Section: Discussionmentioning
confidence: 90%
“…11,41 Interestingly and in agreement with previous studies, protein expression was higher in the non-aggressive biological behaviour group (62.9% vs. 48.2%). 11,42 The p63 protein is known to be overexpressed in different malignant tumours including cutaneous tumours. [43][44][45][46] Other authors have found that >10% of p63-positive cells is associated with worse prognosis in MCC, and that tumours expressing p63 correlate with reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of immunohistochemistry, sentinel lymph nodes harboring single cells and small aggregates of micrometastatic MCC can be discerned 11,12 . Recently, we showed that vascular invasion represents an early event in MCC progression and that lymphatic vascular invasion was observed even in small tumors 13 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recently, we showed that vascular invasion represents an early event in MCC progression and that lymphatic vascular invasion was observed even in small tumors. 13 SLNB typically involves only one or two lymph nodes. We noted an increase in the number of sentinel lymph nodes obtained after our department made a protocol change.…”
Section: Discussionmentioning
confidence: 99%
“…31 Although typically correlated with larger tumor size, LVI has been demonstrated in MCCs as small as 0.3 cm. 32 The ability of MCC to spread very early may account for the unusual aggressiveness of this malignancy. The strong association of LVI with poor prognosis in several cohorts may lead to its incorporation into the next staging algorithm.…”
Section: Prognosismentioning
confidence: 99%